Influence of environmental factors on germination and seedling emergence of Melilotus indicus - DEVI, SUDESH; HOODA, V S; SINGH, SAMUNDER; MOR, V S; THAKRAL, S K (The Indian Journal of Agricultural Sciences, 2020)
To find out the effect of temperature, osmotic stress, light, pH, salt stress, burial depth, mulching and flooding duration on seed germination and seedling emergence of Melilotus indicus, laboratory and screen house experiments were conducted at CCSHAU, Hisar, during rabi seasons of 2015-16 and 2016-17. All the experiments were conducted in a completely randomized design with each treatment having four replications. Based on research results, it was observed that the optimum temperature range for the germination of M. indicus was 15-30oC day temperature and 10-20oC night temperature. It was more sensitive to moisture stress, as its seed germination decreased from 95% to 38% with increasing moisture stress (from 0 to -1.2 MPa), whereas it was less sensitive to salt stress: as more than 50% seed germination occurred at 125 mM NaCl salt concentration. The optimum pH for its seed germination (90%) was neutral (pH 7). It was non-photoblastic in nature, as dark and light period had no significant effect on its seed germination. The optimum burial depth for higher seedling emergence was 1 cm (>90%), but its emergence decreased as burial depth increased further. The seedling emergence was reduced by the application of rice straw as mulch, though a high amount (4 to 10 t/ha) of straw was required to suppress its emergence significantly. Continuous flooding for different durations significantly reduced the seedling emergence of M. indicus over no-flooding condition, and was not able to emerge after 32 days of continuous flooding. The information gained from this study would help in developing effective weed management strategy against M. indicus.